Tantangan Manajerial dan Problematika Pelaksanaan Kurikulum Merdeka: Studi Kualitatif pada TK di Desa Teluk Dalam - Ratih, Sri; Malik, Lina Revilla; Fajriani, Kartika (Pendagogia: Jurnal Pendidikan Dasar, 2026)
The Merdeka Curriculum is designed to foster independent potential in students by strengthening Pancasila character, though its implementation still faces various obstacles and is best executed through school-based management. This qualitative study aims to identify the aspects requiring improvement and the specific challenges encountered in implementing the Merdeka Curriculum at kindergartens in Teluk Dalam Village, Tenggarong Seberang District, Kutai Kartanegara Regency, with respondents comprising teachers, principals, and parents. The results indicate that the management and administration of education based on the Merdeka Curriculum are the most vital components to address; furthermore, implementation is hindered by the teachers' need for a more comprehensive understanding of the curriculum and the requirement for more complete infrastructure tailored to school needs. Consequently, it is recommended that the government evaluate the curriculum's success to ensure its long-term effectiveness.